Investigate the relation between Adiponectin gene variants and cardiovascular comorbidities and diabetes - AT, Eissa (International Journal of Health Sciences, 2016)
Abstract Objectives: This study aimed to study the relationship between the adiponectin gene and coronary artery disease as well as myocardial infarction, hypertension and diabetes in the Saudi population in Riyadh. Methods: This was a cohort study of Saudi patients from the Coronary Artery Disease (CAD) registry maintained at King Faisal Specialist Hospital and Research Centre. Samples were genotyped for target Single Nucleotide Polymorphisms (SNPs) by real time polymerase chain reaction (PCR). Furthermore, Chi Square test was used for comparing the variables. Results: Out of 860 CAD patients compared with 467 non-CAD. The prevalence of the minor G allele of +45T>G in CAD patients was 934 compared to 786 in controls, and it shows no significant difference (p=0.598) between the two groups. The possibility tested that this variant might be associated with one or more of the CAD risk factors, such as hypertension, myocardial infarction, hypertension and diabetes mellitus. Nevertheless, the study did not show any significance between the two groups in CAD, gender and hypertension. On the other hand, the difference in MI was borderline and significant in diabetes mellitus. Conclusions: This study showed a relationship between adiponectin and diabetes only as compared to results from other countries which also showed relationship with coronary artery disease, myocardial infarction and hypertension.Â Key words: Adiponectin, Cardiovascular, genetics, Diabetes